Audiological outcome of stapes surgery for far advanced cochlear otosclerosis. Issue 11 (6th September 2017) - Heining, C; Banga, R; Irving, R; Coulson, C; Monksfield, P
Abstract: Background: Patients with advanced otosclerosis can present with hearing thresholds eligible for cochlear implantation. This study sought to address whether stapes surgery in this patient group provides a clinically significant audiological benefit. Objectives: To assess pre- and post-operative hearing outcomes of patients with advanced otosclerosis, and to determine what proportion of these patients required further surgery including cochlear implantation. Methods: Between 2002 and 2015, 252 patients underwent primary stapes surgery at our institution. Twenty-eight ears in 25 patients were deemed to have advanced otosclerosis, as defined by pure audiometry thresholds over 80 dB. The patients' records were analysed to determine audiological improvement following stapes surgery, and assess whether any further surgery was required. Results: The audiological outcome for most patients who underwent primary stapes surgery was good. A minority of patients (7 per cent) required revision surgery. Patients who underwent cochlear implantation after stapes surgery (10 per cent) also demonstrated a good audiological outcome. Conclusion: Stapes surgery is a suitable treatment option for patients with advanced otosclerosis, and should be considered mandatory, before offering cochlear implantation, for those with a demonstrable conductive component to their hearing loss. A small group of patients get little benefit from surgery and subsequently a cochlear implant should be considered.